Energy and thermodynamic performance of LPG as an alternative refrigerant to R-134a in a domestic refrigerator - Ahamed, Jamal Uddin; Saidur, Rahman; Masjuki, Haji Hassan; Sattar, M.A. (Sila Science, 2012)
This paper presents an experimental investigation on the energy and thermodynamics performance of liquefied petroleum gas (LPG) as an alternative refrigerant to R-134a. LPG with 60 propane and 40 butane by mass fraction is used for the performance investigation. Thermodynamics performance such as co-efficient of performance, refrigeration effect, and compressor work, second law efficiency, and exergy losses have been investigated. The results show that LPG can be a possible alternative to R-134a in a domestic refrigerator. It is found that 60g LPG refrigerant has the lowest exergy loss () followed by 80g LPG. Highest exergy loss has been found when R134a is used as a refrigerant in a domestic refrigerator.